Industry 4.0 from the MIS Perspective - Gülseçen, Sevinc; Ayvaz Reis, Zerrin; Gezer, Murat; Erol, Çigdem (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2019)
Nowadays, an end-to-end industrial transformation called Industry 4.0 sets new goals for manufacturing and impacts on business outcomes. With some of its characteristic elements such as IoT (Internet of Things), digital twin simulation models, advanced robots, big data analytics, and virtual/augmented reality, Industry 4.0 is «de facto» going further. The book aims to provide relevant theoretical frameworks and the latest empirical research findings in the area of Management Information Systems (MIS) with the scope of Industry 4.0. The strategic role of Industry 4.0 in the distributed business environment and the necessity to protect and properly utilize its key elements at different levels of organizations as well as in society are discussed.